2007
DOI: 10.1073/pnas.0605139104
|View full text |Cite
|
Sign up to set email alerts
|

Effects of lengthscales and attractions on the collapse of hydrophobic polymers in water

Abstract: We present results from extensive molecular dynamics simulations of collapse transitions of hydrophobic polymers in explicit water focused on understanding effects of lengthscale of the hydrophobic surface and of attractive interactions on folding. Hydrophobic polymers display parabolic, protein-like, temperature-dependent free energy of unfolding. Folded states of small attractive polymers are marginally stable at 300 K and can be unfolded by heating or cooling. Increasing the lengthscale or decreasing the po… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

17
175
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 113 publications
(195 citation statements)
references
References 60 publications
17
175
1
Order By: Relevance
“…The temperature and monomer size dependence of ΔG hyd are consistent with hydrophobic polymer unfolding simulations from Athawale et al (27). Their work suggests that the turnover behavior of ΔG hyd is present only when a Lennard-Jones attraction between polymer and water is introduced.…”
Section: Discussionsupporting
confidence: 73%
See 2 more Smart Citations
“…The temperature and monomer size dependence of ΔG hyd are consistent with hydrophobic polymer unfolding simulations from Athawale et al (27). Their work suggests that the turnover behavior of ΔG hyd is present only when a Lennard-Jones attraction between polymer and water is introduced.…”
Section: Discussionsupporting
confidence: 73%
“…Furthermore, it was pointed out that the turnover temperature is much more sensitive to the size of the solute than the attraction between solute and solvent (28). The length of the polymer used in the experiment reported here is much greater (hundreds of nanometers) than the 25 mer (∼4 nm) used in the simulation from Athawale et al (27). As a result, the experiment does not probe the finite size effect as in the work of Athawale et al In addition, because both area and volume of the extended polymer are proportional to the extended chain length, the experiment cannot directly test whether the extended polymer ΔG hyd is area or volume dependent.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…Numerous studies a) Electronic mail: chandler@berkeley.edu. of hydrophobicity 4,14,[23][24][25][26][27][28][29][30][31][32][33] have shown that rare solvent motions and dewetting transitions in confining environments play a critical role in solute assembly and function. Our model adequately captures these rare and important fluctuations.…”
Section: Introductionmentioning
confidence: 99%
“…Examples of drying-induced phenomena include the hydrophobic collapse of a polymer chain (25)(26)(27), dewetting-induced attractive interactions studied in detail by Berne, Zhou, and coworkers in the collapse of multidomain proteins and hydrophobic particles (28)(29)(30), and large hydrodynamic slip lengths at the solid-water interface (31)(32)(33).…”
mentioning
confidence: 99%